Drug delivery approaches : perspectives from pharmacokinetics and pharmacodynamics - Berner, Bret; Gordi, Toufigh; Benson, Heather A. E.; Roberts, Michael F. (Hoboken : John Wiley & Sons, Inc., 2021)
Drug Delivery Approaches: Perspectives from Pharmacokinetics and Pharmacodynamics delivers a thorough discussion of drug delivery options to achieve target profiles and approaches as defined by physical and pharmacokinetic models. The book offers an overview of drug absorption and physiological models, chapters on oral delivery routes with a focus on both PBPK and multiple dosage form options. It also provides an explanation of the pharmacokinetics of the formulation of drugs delivered by systemic transdermal routes. The editors have included practical and accessible resources that address the biological and delivery approaches to pulmonary and mucosal delivery of drugs. Emergency care settings are also described, with explorations of the relationship between parenteral infusion profiles and PK/PD. The future of drug delivery is addressed via discussions of virtual experiments to elucidate mechanisms and approaches to drug delivery and personalized medicine
Keywords: Drug delivery systems; Pharmacokinetics; Drugs -- Physiological effect